Associations with metabolites in Chinese suggest new metabolic roles in Alzheimer's and Parkinson's diseases. (19th October 2019) - Chai, Jin-Fang; Raichur, Suryaprakash; Khor, Ing Wei; Torta, Federico; Chew, Wee Siong; Herr, Deron Raymond; Ching, Jianhong; Kovalik, Jean-Paul; Khoo, Chin Meng; Wenk, Markus R; Tai, E Shyong; Sim, Xueling
Abstract: Metabolites are small intermediate products of cellular metabolism perturbed in a variety of complex disorders. Identifying genetic markers associated with metabolite concentrations could delineate disease-related metabolic pathways in humans. We tested genetic variants for associations with 136 metabolites in 1954 Chinese from Singapore. At a conservative genome-wide threshold (3.7 × 10 −10 ), we detected 1899 variant–metabolite associations at 16 genetic loci. Three loci ( ABCA7, A4GALT, GSTM2 ) represented novel associations with metabolites, with the strongest association observed between ABCA7 and d18:1/24:1 dihexosylceramide. Among 13 replicated loci, we identified six new variants independent of previously reported metabolite or lipid signals. We observed variant–metabolite associations at two loci ( ABCA7, CHCHD2) that have been linked to neurodegenerative diseases. At SGPP1 and SPTLC3 loci, genetic variants showed preferential selectivity for sphingolipids with d16 (rather than d18) sphingosine backbone, including sphingosine-1-phosphate (S1P). Our results provide new genetic associations for metabolites and highlight the role of metabolites as intermediate modulators in disease metabolic pathways.